REFLEKSI VISI LEMBAGA PENDIRI DALAM MODEL PENDIDIKAN DAN CIRI KHAS SEKOLAH ISLAM - Anam, Saipul; Alif Haidir Aziz, M.; Fatahillah, M.; Khairul Anam, Rifqi (As-Sulthan Journal of Education, 2026)
This study examines how the founding institution’s vision functions as the foundation for shaping the distinctive characteristics of Islamic schools through their educational models, curricula, and school cultures. Departing from the gap between theoretical ideals and actual practices, this research highlights that many Islamic schools claim a particular identity without fully internalizing the ideological values of their founding organizations. Through a reflective and comparative library-based analysis, this study reviews literature on various Islamic educational organizations such as Muhammadiyah, Nahdlatul Ulama (NU), Al-Irsyad, Hidayatullah, and Integrated Islamic Schools which demonstrates variations in educational models based on the ideological orientation of their founders. The findings affirm that the founders’ vision acts as an ideological driver influencing the selection of educational models (integrative, holistic, tahfiz, modern pesantren, or full-day school), the development of Islam-oriented curricula, and the formation of religious school culture as institutional identity. This study offers a conceptual framework that explains the causal relationship between the founders’ vision and educational practices in Islamic schools, filling the gap in previous comparative studies that typically focused on single organizations. The results underscore that consistency between the founders’ vision and its educational implementation is a key determinant of the character and uniqueness of Islamic schools.